(untitled) (Journal of Governance and Development (JGD), 2023)
Recycling is a practice decisive to a better future to avoid pollution that could change the world landscape and affect the lives of future generations. This study was conducted to examine the knowledge and awareness of the Ulu Muda, Sik community on recycling practices. The descriptive study used random probability sampling whereby the sample size of the study was 30 respondents. Questionnaires were used as a medium to measure the level of knowledge and awareness of the community in the study area. In addition, interviews were also conducted to get an accurate picture and information on recycling practices among fishermen, traders and the local community. The findings of the study found that the respondents strongly agreed with the recycling activities carried out to preserve their environment although they have a moderate level of knowledge and awareness regarding recycling practices. In addition, an eco-friendly lifestyle is not yet a culture despite the environment is an important resource in ensuring the well-being of life. In this regard, its care and conservation should be on the agenda and practice of both urban and rural residents. Comprehensive involvement from all parties will provide an opportunity for them to practice, appreciate and cultivate environmentally friendly and recycling features in the school environment, home, local community, community and finally at the Malaysian national level. In conclusion, in order to raise awareness of recycling practices in the community, education and information need to be increased to the community.